Genetic distance of Malaysian mousedeer based on mitochondrial DNA cytochrome oxidase I (COI) and D-loop region sequences - Mohamad Azam Akmal, Abu Bakar; Rovie Ryan, Jeffrine Japning; Ahmad, Ampeng; Salmah, Yaakop; Shukor, Md Nor; Badrul Munir, Md Zain (2018)
Mousedeer is one of the primitive mammals that can be found mainly in Southeast-Asia region. There are two species of mousedeer in Malaysia which are Tragulus kanchil and Tragulus napu. Both species can be distinguish by size, coat coloration, and throat pattern but clear diagnosis still cannot be found. The objective of the study is to show the genetic distance relationship between T. kanchil and T. napu and their population based on mitochondrial DNA (mtDNA) cytochrome oxidase I (COI) and D-loop region. There are 42 sample of mousedeer were used in this study collected by PERHILITAN from different locality. Another 29 D-loop sequence were retrieved from Genbank for comparative analysis. All sample were amplified using universal primer and species-specific primer for COI and D-loop genes via PCR process. The amplified sequences were analyzed to determine genetic distance of T. kanchil and T. napu. From the analysis, the average genetic distance between T. kanchil and T. napu based on locus COI and D-loop were 0.145 and 0.128 respectively. The genetic distance between populations of T. kanchil based on locus COI was between 0.003-0.013. For locus D-loop, genetic distance analysis showed distance in relationship between west-coast populations to east-coast population of T. kanchil. COI and D-loop mtDNA region provided a clear picture on the relationship within the mousedeer species. Last but not least, conservation effort toward protecting this species can be done by study the molecular genetics and prevent the extinction of this species.